STANDARDS OF BELARUS IN THE FIELD OF PHOTOMETRY - N. V. Bakovets; S. V. Niknenko; D. V. Skums; O. B. Tarasova (Приборы и методы измерений)
The article introduces a standard base of Belarus in the field of photometry. Scientific research conducted on the standards can be interest for professionals working in the areas of mechanical engineering, instrument, medicine, agriculture and other.